A novel proton transfer mechanism in the SLC11 family of divalent metal ion transporters - Pujol-Giménez, Jonai (Sci Rep, 2017)
In humans, the H(+)-coupled Fe(2+) transporter DMT1 (SLC11A2) is essential for proper maintenance of iron homeostasis. While X-ray diffraction has recently unveiled the structure of the bacterial homologue ScaDMT as a LeuT-fold transporter, the exact mechanism of H(+)-cotransport has remained elusive. Here, we used a combination of molecular dynamics simulations, in silico pK (a) calculations and site-directed mutagenesis, followed by rigorous functional analysis, to discover two previously uncharacterized functionally relevant residues in hDMT1 that contribute to H(+)-coupling. E193 plays a central role in proton binding, thereby affecting transport properties and electrogenicity, while N472 likely coordinates the metal ion, securing an optimally “closed” state of the protein. Our molecular dynamics simulations provide insight into how H(+)-translocation through E193 is allosterically linked to intracellular gating, establishing a novel transport mechanism distinct from that of other H(+)-coupled transporters.